The use of cbers (China-Brazil earth resources satellite) to trace the dynamics of total suspended matter at an urbanized coastal area - Giannini, Maria Fernanda Colo [UNESP]; Harari, Joseph; Ciotti, Aurea Maria (FapUNIFESP (SciELO), 2017)
The distribution of organic and inorganic particles in the water column, or the total suspended matter (TSM), responds to local and remote oceanographic and meteorological processes, potentially impacting biogeochemical cycles. In shallow coastal areas, where particles have distinct origins and compositions and vary in different time scales, the use of remote sensing tools for monitoring and tracing this material is highly encouraged due to the high temporal and spatial data resolution. The objective of this work was to understand the variability of in situ TSM at Santos Bay (Southeastern Brazil) and its response to oceanographic and meteorological conditions. We also aimed to verify the applicability of the satellite data from CBERS-2 sensor in order to map the dynamics of TSM in this region. Our results have shown that the distribution of TSM in Santos Bay varied consistently with winds, currents and tidal cycles, with significant relationships emphasizing the role of south-western winds and spring tides. Neap tides and eastern winds, along with rainfall, play an important role in the input of organic matter into the bay. In conclusion, our analyses showed that the main patterns observed in situ regarding the responses of TSM to the ocean-meteorological processes could be reproduced in the CBERS-2 satellite data, after simple and standard methods of images processing. TSM data retrieval from CBERS-2 or other satellite sensors were shown to be feasible, becoming an essential tool for synoptic observations of the composition and quality of water, especially at urbanized and impacted coastal areas.
Keywords: CBERS program; Remote sensing; Santos Bay; Suspended matter